One-year treatment follow-up of plantar fasciitis: radial shockwaves vs. conventional physiotherapy (Clinics, 2013)
OBJECTIVE: To compare radial shockwave treatment with conventional physiotherapy for plantar fasciitis after 12 months of follow-up. METHOD: This was a randomized, prospective, comparative clinical study. Forty patients with a diagnosis of plantar fasciitis were divided randomly into two treatment groups: group 1, with 20 patients who underwent ten physiotherapy sessions comprising ultrasound, kinesiotherapy and guidance for home-based stretching; and group 2, with 20 patients who underwent three applications of radial shockwaves, once a week, and guidance for home-based stretching. All patients were assessed regarding pain and functional abilities before treatment, immediately after and 12 months after treatment. The mean age was 49.6 ±11.8 years (range: 25-68 years), 85% were female, 88% were overweight, 63% were affected bilaterally, and 83% used analgesics regularly. RESULTS: At the 12-month follow-up, both treatments were effective for improving pain and functional ability among the patients with plantar fasciitis. The improvement with shockwaves was faster. CONCLUSION: Shockwave treatment was not more effective than conventional physiotherapy treatment 12 months after the end of the treatment.